Unknown Input Observer Design for Vehicle Lateral Dynamics Described by Takagi–Sugeno Fuzzy Systems - El Aiss-Berazouq, H; Zoulagh, T (John Wiley and Sons Ltd, 2022)
This article discusses the problem of an unknown input observer for nonlinear lateral dynamic systems. Takagi–Sugeno fuzzy models have been used to represent the vehicle lateral system with parameters uncertain. The observer used is well suited to estimate the vehicle state and actuator/sensor faults, simultaneously. By using Finsler s lemma, the conditions obtained are expressed through linear matrix inequality constraints. Finally, the results of the simulation clearly show the importance and effectiveness of the proposed approaches. © 2021 John Wiley & Sons Ltd.